Factors Related to Polygamy Family in Pidie District - Finaul Asyura; Marthoenis Marthoenis; Maidar Maidar (Universitas Syiah Kuala, 2021)
Polygamy is a marriage that has been carried out by many people from various circles. During 2001, there were 234 cases of violence against wives. Data on victims reveals 5.1% of polygamy in secret, 2.5% of official polygamy, 36.3% of victims of cheating, 2.5% left by their husbands, 4.2% divorced, 0.4% as a second wife, and Another 0.4% as a dating park. Types of violence reported include economic violence as much as 29.4%; physical violence 18.9%; sexual violence 5.6%; and 46.1% psychological violence. There are still cases of polygamous families in Pidie Regency which can cause rifts in the household and can even cause feelings of sadness, jealousy, prolonged stress, and hatred because they feel they have been betrayed by their husbands. This study aims to determine the factors associated with polygamous families in Pidie District. The design of this research is case control. The research location is in Pidie Regency,. The sample in this study were 30 polygamous families, both first, second, third and fourth wives and as many as 60 families who were not polygamous. The results of the study that the most dominant variable on the incidence of polygamous families was a history of 12 times the disease. Expecting women to maintain attraction to their husbands so that husbands do not have a tendency to approach other women.